ANALISIS SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K3) STUDI KASUS DI KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - Lukum, Wahidin; Malo, Fadlan; Arsana, I Kadek Satria (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
The implementation of Occupational Health and Safety Management Systems is a crucial aspect in ensuring the sustainability and productivity of industries, including the bottled drinking water sector. However, many companies have yet to adopt safety standards in a systematic and continuous manner. This study aims to evaluate the extent of OHSMS implementation in an AMDK company located in Tilongkabila District and to identify influencing factors. The findings reveal that the OHS practices in the company are not yet optimal and do not comply with ISO 45001 standards. The absence of a dedicated OHS unit, low worker competency in safety matters, and weak management commitment are the main obstacles to effective implementation. These findings imply the need for a more integrative managerial approach and the strengthening of safety culture as part of an industrial sustainability strategy. This study is limited by its narrow geographic scope and qualitative, which does not include quantitative measurement of OHSMS effectiveness. Future research is recommended to employ mixed methods and involve multiple companies to achieve broader and deeper generalization. This research highlights that the success of OHSMS strongly depends on the synergy between policy, training, and an organizational culture that upholds safety as a core value.